Cu, Mo and Fe content in shrubs and subshrubs of the Arid Pampas Region (Semiárida, 2020)
Since march 1987 and along the year several forage cuts have been achieved over 26 shrubs and small shrubs species with mean growing in the Pampean Arid Region, in order to analyze Cu, Mo and Fe. The Cu a mouths resulted acceptable, the ratio Cu/Mo overcame 2:1 in all species, except for Prosopis alpataco and Bredemeyera microphyla. Fe showed wide variation among species and also between cuts.